JAEPL, Vol. 18, Winter 2012-2013 - Joonna Smitherman Trapp; Brad Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
Essays Douglas Hesse - Writing and Time, Time and the Essay Liz Rohan - The Rainbow Connection: Theorizing the Efficacy of Private Texts Christy I. Wenger - Writing Yogis: Breathing Our Way to Mindfulness and Balance in Embodied Writing Pedagogy Lavinia Hirsu - Reflections on Accidental Testimonies and Spectacular Witnesses Heather Trahan - Queers, Cupid's Arrow, and Contradictions in the Classroom: An Activity Theory Analysis Shelly Sanders & B. Cole Bennett - Gatekept: Inviting Creative Community Literacy Out of the Box Richard Leo Enos - Outside the Box and onto a Dusty Trail SPECIAL SECTION: Administration, Ethics, and Spirituality Paul Puccio - Even Administrators Have Souls Tom Truesdell - The Communally Focused Writing Center Elizabeth Vander Lei - Renovating My Academic Administration Beth Daniell - Telling the Truth as WPA Book Reviews Judy Halden-Sullivan - Paradigm Shifts Lauren DiPaula - Price, Margaret. Mad At School: Rhetorics of Mental Disability and Academic Life. Ann Arbor: University of Michigan Press, 2011. William Archibald - Thomas, Douglas and John Seely Brown. A New Culture of Learning: Cultivating the Imagination for a World of Constant Change. Charleston, SC: CreateSpace, 2011. Noam Scheindlin - Vandermeulen, Carl. Negotiating the Personal in Creative Writing. Bristol: Multilingual Matters, 2011. Martin Cockroft - Wilhelm, Jeffrey D. and Bruce Novak. Teaching Literacy for Love and Wisdom: Being the Book and Being the Change. NY: Teachers College Press, 2011. Connecting Helen Walker - Trust, and Gaps Carl Vandermeulen - Proverbs for Poetry Class Louise Morgan - TJ, Whom I Like Very Much Jill Moyer Sunday - History Lesson 101 Tony Mayo - Shawn